A Systematic Review on the Outcomes of the Fillet Flap in Treating Diabetic and Ischemic Forefoot Ulcers. Issue 3 (August 2021) - Yammine, Kaissar; Assi, Chahine
Background: Diabetic and ischemic foot ulcers are difficult to heal, and the mastering of numerous treatment methods is imperative to achieve healing. One of these methods is the fillet toe flap used to cover specific diabetic wounds of the forefoot associated with toe osteomyelitis. Instead of amputating the infected toe, phalanges are removed while keeping the viable surrounding soft tissue. Methods: A systematic review was performed searching electronic databases up to October 2019 to identify relevant articles reporting the outcomes of the fillet flap in forefoot ulcers of patients with diabetes or peripheral artery disease. All study designs were included. The healing rate was the primary outcome. Secondary outcomes were the time to heal, ulcer recurrence, and complication rates of such infection, partial necrosis, and total necrosis. Results: The 8 studies that met the inclusion criteria were all case series or case reports, with a total of 28 patients including 29 flaps. The mean healing rate was 92.8% (2/29); in both cases, total necrosis was due to infection (7.2%). No ulcer recurrence or partial necrosis was noted. Conclusions: Though having limited indications, the fillet flap illustrates the full optimization of the available resources for wound coverage. The consistent presence of an axial vessel makes the fillet flap a reliable local flap to be used in specific circumstances where the loss of a toe is unavoidable. Further research is needed with large prospective controlled trials to support the findings of the review.